1700 Expression of the Nuclear Factor of Activated T Cells MRNA in Human Fetal Lung. (October 2012) - Ramos, CG; Sun, X; Gonzalez-Bosc, L
Abstract : Background and Aims: The nuclear factor of activated T cells (NFAT) is a family of four transcription factors (c1, c2, c3 and c4) involved in vascular smooth muscle differentiation, contractility and hypertrophy. NFATc3 is required for hypoxia-induced pulmonary hypertension and for murine vascular patterning. High pulmonary vascular tone is necessary in the fetus and vasoconstrictors, such as endothelin-1 (ET-1), are required. ET-1 is a potent activator of NFAT but the role of NFAT in human lung vascular development is not known. We aim to study NFAT expression during mid-gestation in the human fetal lung. Methods: Human fetal lung tissue from 10 to 24 weeks of gestation was collected following elective termination (N:40). Gene expression of the NFAT isoforms c1, c2, c3 and c4 was measured in fetal lung tissue with qRT-PCR, normalized to GAPDH. Statistical analysis was performed using Spearman non-parametric correlation coefficient. Results: In the human fetal lung, NFATc1 expression increased with increasing gestational age (R 2 = 0.2708). NFATc2 expression remained stable (R 2 = 0.0117). NFATc3 expression increased (R 2 = 0.1802). Conversely, NFATc4 expression decreased with advancing gestational age (R 2 = 0.3774). Conclusion: The NFAT isoforms are expressed during mid-gestation in the human fetal lung showing different patterns of expression. NFATc1 and NFATc3 expression increased suggesting a possible role in developmental vascular patterning in humans. NFATc4 expression decreased significantly and NFATc2 expression remained unchanged, requiring further research. These results suggest that NFAT is involved in fetal vascular development.